2003
DOI: 10.1063/1.1597761
|View full text |Cite
|
Sign up to set email alerts
|

Transport and magnetic properties of La0.7Pb0.3MnO3+x Ag (x=0−20 wt %) nanocomposites

Abstract: Magnetization and transport properties of La0.7Pb0.3MnO3+x Ag (x=0−20 wt %) nanocomposites have been reported. In this Ag-containing colossal magnetoresistive (CMR) La0.7Pb0.3MnO3 composite (referred to as CMR-Ag), conductivity (σ) and metal–insulator transition temperature (Tp) increase with increasing Ag. Electron microscopy and elemental mapping indicated a uniform distribution of Ag nanoparticles/clusters. The enhancement of Tp is accompanied by a reduction of the c-axis lattice constant. Coexistence of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…However, the presence of the grain boundaries in these polycrystalline CMR materials introduces more resistance for the electron transport, which hinders the enhancement of MR indirectly. Recently, it is found [9,10] that by adding Ag in polycrystalline CMR materials, can lead to large room temperature MR if T C of the compounds is near room temperature, as well as to reduction in the resistivity in terms of the modifications of microstructure, electrical and magnetic inhomogeneity on the grain surfaces/boundaries. Based on these achievements, we combined Ag 2 O with polycrystalline La 0.67 Ba 0.33 Mn 0.88 Cr 0.12 O 3 (LBMCO) synthesized by sol-gel method.…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of the grain boundaries in these polycrystalline CMR materials introduces more resistance for the electron transport, which hinders the enhancement of MR indirectly. Recently, it is found [9,10] that by adding Ag in polycrystalline CMR materials, can lead to large room temperature MR if T C of the compounds is near room temperature, as well as to reduction in the resistivity in terms of the modifications of microstructure, electrical and magnetic inhomogeneity on the grain surfaces/boundaries. Based on these achievements, we combined Ag 2 O with polycrystalline La 0.67 Ba 0.33 Mn 0.88 Cr 0.12 O 3 (LBMCO) synthesized by sol-gel method.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the effect of Ag addition on the structural, magnetic, transport and MR properties in many manganite/Ag type composite systems has been investigated [15][16][17][18][19][20][21]. All the results have showed that the addition of Ag highly influences the grain size and nature of the grain boundary.…”
Section: Introductionmentioning
confidence: 99%
“…2 shows the temperature dependence of zero-field resistivity ( ) for the composites has been measured in the temperature region from 5 to 300 K. Results show that: (i) decrease with Ag addition; (ii) adding Ag in LCMO sharps the peak and shifts the peak temperature of , T p , to higher temperature. Pal et al [10] shown that this behavior of present nanocomposite samples, with higher Ag content, can be explained by considering the coexistence of interfacial tunneling and spin related intrinsic transport at the grain boundaries.…”
Section: Resultsmentioning
confidence: 86%
“…Recently, a great deal of experiments have indicate that the Agdoped manganites can exhibit an improved T C , metal-insulator transition temperature (T p ), temperature coefficient of resistance (TCR) and an enhanced extrinsic MR effect [9][10][11][12][13]. All the abovementioned results indicate that Ag-doped samples have improved MR effect and a significant low-field magnetoresistance (LFMR) as compared with the undoped counterpart.…”
Section: Introductionmentioning
confidence: 97%